THE FINANCIAL PERFORMANCE OF BANK SYARIAH INDONESIA: PRE- AND POST-MERGER - Muchtar, Masruri; Puspita, Desy; Amalia, Euis (TRIKONOMIKA, 2024)
Due to the merger, Bank Syariah Indonesia (BSI) recorded total assets of IDR 240 trillion. This study examines whether there are differences between the pre-and post-merger in the financial performance of BSI in terms of liquidity, solvency, and profitability using Wilcoxon signed test and paired sample t-test. This study finds significant differences in the level of liquidity and profitability of BSI's financial performance, while there is no significant difference in the level of solvency. This result implies that BSI's efficiency in managing business increases; therefore, the operational costs might be reduced, and the operating income tends to grow. Although the financing-to-debt ratio (FDR) is moderate, BSI still needs to improve the effectiveness of its fund distribution. This study contributes to the literature on mergers and acquisitions in the banking sector, particularly for Islamic banks, by providing new insight into its impact on financial performance.